Noncoding RNA gene silencing through genomic integration of RNA destabilizing elements using zinc finger nucleases - Gutschner, Tony; Baas, Marion; Diederichs, Sven (Genome research, 2011)
An international, peer-reviewed genome sciences journal featuring outstanding original research that offers novel insights into the biology of all organisms